Kontribusi Makanan Jajanan, Indeks-Massa-Tubuh dan Kadar Hb Remaja Putri, Pesantren Ibadurrahman Tangerang - Sari, Nirmala; Mulyani, Erry Yudhya (Lembaga Penerbitan Unversitas Esa Unggul, 2011)
AbstractSnack is a mixture of various processed foodstuffs in the form of food processed with simultaneously. Snack can contribute nutrients to fulfil the Recommended Dietary Allowance. The aims of this study was to determine the relationship between the contribution nutrient of snack with the body mass index and hemoglobin levels in adolescent girls. The design of this study is cross-sectional.Sample of this study is mostly boarding students Ibadurrahman. We used purposive sampling and total of sample are 99 respondents. Statistic test used Pearson correlation test. Mostly respondents aged 16 years, the body weight is (49.1 ± 4.7)kg, height is (150.9 ± 5.2)cm, hemoglobin level is (11.8 ± 0.6)mg/dl, and the nutritional status of the normal is (21.5 ± 2.8). The contributions energy of snack is (66.5 ± 9.1)%, protein is (66.1 ± 11.2)%, Fat is (82.7 ± 10.7)%, Carbohydrate is (57.4 ± 9.5)%, Fe is (70.3± 12.9)%, Vitamin C is (93.3±10.1)%, Vitamin A is (93.3 ± 10.0)%, and Folic Acid is (73.3 ± 12.6)%. There is no relationship between the contribution energy of snack (r = 0.044), protein (r = 0.021), fat (r = 0.102), carbohydrate (r = -0006) and the body mass index (p ≥ 0.05). There is no relationship between the contribution energy of snack (r = 0.026), protein (r = 0.007), Fe (r = 0.052), vitamin C (r = 0.123), vitamin A (r = 0.167), folic acid (r = 0.064) and Hb levels (p ≥ 0.05). More than half of average intake of nutrients contribution comes from snack. However, we need to increase the cost of eating at boarding school which can give more variation of food and the student wants to consume it.Key Words: Contribution nutrient of snack, Body Mass Indeks, Hb level AbstrakMakanan jajanan merupakan campuran dari berbagai bahan makanan yang diolah secara bersamaan dalam bentuk olahan. Makanan jajanan dapat memberi kontribusi zat gizi untuk memenuhi AKG. Penelitian ini bertujuan untuk mengetahui hubungan kontribusi zat gizi makanan jajanan dengan Indeks Massa Tubuh dan Kadar Hb pada remaja putri. Desain penelitian ini cross-sectional dengan sampel adalah sebagian siswi pesantren Ibadurrahman. Pengambilan sampel dilakukan secara purposive sampling dan didapat 99 responden. Uji statistik menggunakan uji korelasi Pearson. Sebagian Besar responden berumur 16 tahun, memiliki berat badan (49.1±4.7)kg, rata-rata tinggi badan (150.9±5.2)cm, Kadar Hb (11.8±0.6)mg/dl, dan berstatus gizi rata-rata normal (21.5±2.8). Kontribusi makanan jajanan didapat asupan energi (66.5±9.1)%, protein (66.1±11.2)%, Lemak (82.7±10.7)%, Karbohidrat (57.4±9.5)%, Fe (70.3±12.9)%, Vitamin C (93.3±10.1)%, Vitamin A (93.3±10.0)%, dan Asam Folat (73.3±12.6)%. Tidak ada hubungan antara kontribusi energi (r=0.044), protein (r=0.021), lemak (r=0.102), Karbohidrat (r=-0.006) dengan Indeks Massa Tubuh (p≥0.05). Tidak ada hubungan antara kontribusi energi (r=0.026), protein (r=0.007), Fe (r=0.052), vitamin C (r=0.123), vitamin A (r=0.167), asam folat (r=0.064) dengan kadar Hb (p≥0.05). Lebih dari separuh rata-rata asupan kontribusi zat gizi berasal dari makanan jajanan. Sehingga perlu adanya peningkatan biaya makan di Pesantren agar makanan lebih bervariasi dan menarik minat siswi dalam mengkonsumsinya. Kata Kunci: Kontribusi makanan jajanan, Indeks-Massa-Tubuh, kadar Hb